Investigation of metal β-diketonates as parent materials for reference samples - Yurchenko, O.I.; Shevtsov, N.I.; Mikhailova, L.I.; Belikov, K.N.; Titova, N.P.; Shkumat, A.A. (Functional Materials, 2005)
Stability of synthesized lead, cadmium and chromium (III) β-diketonates and mercury
(I) dimedonate in solid state and in diluted solutions was investigated by titrimetry and inductively coupled plasma optical emission spectrometry. It was shown, that the solid samples are stable during 5 years and the solutions keep the concentration for 4 months. Metal acetylacetonates are recommended as parent substances for manufacturing of reference samples used for calibration of analytical instruments and accuracy control. Исследована устойчивость синтезированных β-дикетонатов свинца, кадмия, хрома
(III) и димедоната ртути (I) в твердом состоянии и в разбавленных растворах методами титриметрического анализа и атомно-эмиссионной спектрометрии с индукционной плазмой. Показано, что твердые образцы устойчивы в течение 5 лет, а разбавленные растворы сохраняют свою концентрацию 4 месяца. Ацетилацетонаты металлов рекомендованы в качестве исходных веществ для изготовления стандартных образцов состава при градуировке аналитических приборов и контроля правильности результатов анализа. Дослiджено стiйкiсть синтезованих β-дикетонатiв свинцю, кадмiю, хрому (III) та димедонату ртутi (I) у твердому станi та у розведених розчинах методами титриметричного аналiзу та атомно-емiсiйної спектрометрiї з iндукцiйною плазмою. Показано, що твердi зразки є стiйкими на протязi 5 рокiв, а розведенi розчини зберiгають концентрацiю 4 мiсяцi. Ацетилацетонати металiв рекомендовано як вихiднi речовини для виготовлення стандартних зразкiв складу при градуюваннi аналiтичних приладiв та проведеннi контролю правильностi результатiв аналiзу.